Biomarkers and Diagnostic Testing for Renal Disease in Sjogren's Syndrome - Ramponi, Giacomo; Folci, Marco; Badalamenti, Salvatore; Angelini, Claudio; Brunetta, Enrico (Frontiers in Immunology, 2020)
Primary Sjogren's syndrome (pSS) is an autoimmune disorder in which lymphocytic infiltration leads to lacrimal and salivary glands dysfunction, which results in symptoms of dryness (xerophthalmia and xerostomia). Extraglandular features are common and may affect several organs. Renal involvement has long been known as one of the systemic complications of pSS. The most classical lesion observed in pSS is tubulointerstitial nephritis (TIN) and less frequently membranoproliferative glomerulonephritis (MPGN), which is related to cryoglobulinemia. In some cases, renal biopsy is necessary for the definitive diagnosis of kidney involvement. Patients may present with proximal renal tubular acidosis, distal renal tubular acidosis and chronic kidney disease. Response to treatment is usually favorable. However, occasionally severe and rarely lethal outcomes have been described. Recently, several case series and cross-sectional studies have been published which investigated the factors associated with renal involvement in pSS and the most accurate screening tests for early detection. The presence of xerophthalmia, anti-SSA and rheumatoid factor positivity, low C3 levels and other features have all shown either positive or inverse associations with the development of renal complications. Serum creatinine, alpha-1-microglobulin, cystatin-C have been evaluated as early detection biomarkers with variable accuracy. More advanced techniques may be necessary to confirm proximal and distal renal tubular acidosis, along with nephrogenic diabetes insipidus. The aim of the current paper is to summarize and critically examine these findings in order to provide updated guidance on serum biomarkers and further testing for kidney involvement in pSS.